The effect of two different intense training protocols on oxidative stress of liver tissue during puberty in male rats - Leila Youzbashi; Parisa Abdollahi; Ahmad Rahmani (Sport Sciences and Health Research)
Background: Intense physical activity increases the production of reactive oxygen species in vital tissues such as the liver and causes oxidative stress.Aim: This study investigates the effect of high-intensity interval training and intense endurance training on oxidative stress of liver tissue in immature male rats during puberty.Materials and Methods: A total of 24 male Wistar rats (aged= 22 days, weight= 60±0.63 g), after one week of acclimatization, were divided randomly into three groups: control, IET, and HIIT. Rats were subjected to a four-week training on an animal treadmill. The effects of training treatment in rat liver were investigated by assaying oxidative stress biomarkers.Results: Comparing to control group, in both training groups significantly lower Malondialdehyde (MDA) was seen ((P(IET)= 0.016/ P(HIIT)= 0.020). However, there were no statistical differences in Glutathione Peroxidase (GPX) (P= 0.463) and total antioxidant capacity (TAC) activity levels (P= 0.194) among groups. HIIT training significantly increased superoxide dismutase (SOD) (P= 0.040) and catalase enzyme (CAT) levels (P= 0.007). IET and HIIT had significantly increased endurance performance (both: P= 0.001).Conclusion: Both training intensities did not lead to an increase in oxidative stress and can be used during puberty.